The Microbiome in Hidradenitis Suppurativa: A Review - Wark, Kirsty J. L. (Dermatol Ther (Heidelb), 2020)
INTRODUCTION: Hidradenitis suppurativa (HS) is a chronic autoinflammatory skin disease. It is characterised by the development of abscesses and nodules in intertriginous anatomical sites. Whilst it is now recognised as an autoinflammatory condition rather than an infective disease, bacteria are implicated in disease pathogenesis. METHODS: We performed a search of the literature from inception to 12 August 2020 using the search terms “hidradenitis suppurativa”, “Verneuil’s disease”, “acne inversa”, “microbiome”, “bacteriology” and “microbiology”. Studies were included if they assessed the cutaneous, gut or oral bacteria, bacteriology or microbiome in hidradenitis suppurativa. RESULTS: Twenty-one studies examining the cutaneous microbiome and two studies examining the gastrointestinal microbiome in HS were identified. No studies examining the oral microbiome in HS were identified. A total of 972 patients and 46 healthy controls were included across studies examining the cutaneous microbiome. A total of 100 patients and 36 controls were included across both gut microbiome studies. Coagulase-negative Staphylococcus, anaerobes such as Porphyromonas and Prevotella, and Staphylococcus aureus species were commonly encountered organisms across the included cutaneous microbiome studies. The studies examining the gut microbiome were limited, with one small study demonstrating an alteration in the gut microbiome composition compared to controls. The other study found no alteration to the gut microbiome in patients with HS compared to those with inflammatory bowel disease (IBD) and HS, and IBD and/or psoriasis. CONCLUSION: Research should be undertaken into the oral microbiome in HS. Further research should be undertaken examining the cutaneous and gut microbiome in HS, and its relationship with documented co-morbidities. Additionally, metagenomics-focused studies may help identify the relationship between microorganisms and host, and this may shed light on new pathways of disease pathogenesis. This may help identify potential future therapeutic targets.